Electrochemical decolorization of Rhodamine B dye: Influence of anode material, chloride concentration and current density - Baddouh, Ali [UNESP] (2018)
Surface water contamination by dyes released from a variety of industries is an environmental problem of great concern. However, electrochemical oxidation is a promising alternative for water treatment. In this paper, we studied the electrochemical oxidation of Rhodamine B (RhB) dye on the Ti/RuO2-IrO2 (DSA®) and SnO2 anodes comparing their efficiencies. The effect of some parameters, such as current density, initial pH (pH0), nature, concentration of electrolyte and temperature at the electrochemical oxidation was investigated evaluating the decolorization and the chemical oxygen demand (COD) removal at optimal conditions. Complete decolorization of RhB was achieved in the presence of chloride ions at different times using both electrodes. An optimum efficiency was obtained at pH 6.5, T°C. Also, the current density of 40cm-2 using the DSA electrode in NaCl 0.05L-1+ Na2SO4 0.1L-1 mixture solution as a supporting electrolyte, 100% color removal and 61.7% chemical oxygen demand removal after 90min of electrolysis were achieved. DSA showed better performance than SnO2 in wide operating conditions and was proved to be more cost-effective and more efficient. The effectiveness of the degradation is explained by indirect electrochemical oxidation, where in the presence of chlorides electrolyte leads to the electro-generation of strong oxidant species, such as Cl2 and ClO- ions, improving the efficiency of treatment at both electrodes.